The Effect of Prolanis Exercise on Reducing Blood Sugar Levels - Faswita, Wirda; Leny Suarni; Anggi Lauviga (Talenta Publisher, 2021)
Diabetes mellitus (DM) is a dangerous disease because it causes many complications. Prolanis Exercise is one of the physical activities for people with Diabetes Mellitus (DM) to lower blood glucose levels. This study aims to determine the effect of prolanis exercise on reducing patients' blood glucose levels in the working area of the southern Namu Ukur Health Center. The Quasi Experiment method with a one-group pretest-posttest design is used as a research design. This study also used a purposive sampling method with 28 respondents. Prolanis Exercise exercises were used as the data collection tool. The results showed that there was an effect of prolanis exercise on decreasing blood glucose levels in people with Diabetes Mellitus (DM) in the working area of the Namu Ukur Health Center with a value of 0.004 (Î±<0.05). Before treatment, blood sugar levels were an average of 270 mg/dL and 257 mg/dL after the treatment. Patients with Diabetes Mellitus (DM) should carry out regular physical activities in routine such as prolanis exercise.